Involvement of Receptor-Mediated S1P Signaling in EGF-Induced Macropinocytosis in COS7 Cells - Matovelo, Shubi Ambwene; Zhang, Lifang; Mohamed, Nesma Nabil Ibrahim; Kajimoto, Taketoshi; Ijuin, Takeshi; Okada, Taro; Nakamura, Shun-Ichi (Kobe journal of the medical sciences, 2020)
Macropinocytosis is a highly conserved cellular process of endocytosis by which extracellular fluid and nutrients are taken up into cells through large, heterogeneous vesicles known as macropinosomes. Growth factors such as epidermal growth factor (EGF) can induce macropinocytosis in many types of cells, although precise mechanism underlying EGF-induced macropinocytosis remains unclear. In the present studies we have shown the involvement of S1P signaling in EGF-induced macropinocytosis in COS7 cells. First, EGF-induced macropinocytosis was strongly impaired in sphingosine kinase isozymes, SphK1 or SphK2-depleted cells, which was completely rescued by the expression of the corresponding wild-type isozyme but not the catalytically inactive one, suggesting the involvement of sphingosine 1-phosphate (S1P) in this phenomenon. Next, we observed that EGF-induced macropinocytosis was strongly inhibited in S1P type 1 receptor (S1P1R)-knockdown cells, implying involvement of S1P1R in this event. Furthermore, we could successfully demonstrate EGF-induced trans-activation of S1P1R using one-molecular fluorescence resonance energy transfer (FRET) technique. Moreover, for EGF-induced Rac1 activation, a step essential to F-actin formation and subsequent macropinocytosis, S1P signaling is required for its full activation, as judged by FRET analysis. These findings indicate that growth factors such as EGF utilize receptor-mediated S1P signaling for the regulation of macropinocytosis to fulfil vital cell activity.